PROFIL KOMPONEN BIOAKTIF TANAMAN KAVA-KAVA (PIPER METHYSTICUM, FORST, F) DARI BERBAGAI LOKASI - Elly Purwanti (Jurnal Gamma, 2010)
The purpoeof this research is to know the profil of bioactive component from root, stem,leaves of cava-cava and the information of which part of plant that give the effect of locomatioeffect and antidepressive by using parameter of immobility duration with swimming method andsleeping duration.Method used in evaluating quality and standart of plant that potentially as herbal medicinethat usually used and information is Thin layer Chromatography (TLC) and High Speed LiquidChromatography (HPLC) ( dashek 1997) Herbal plant that conatins some variuos substances cansupport each other but it can possibly has antagonist effect. This the reason why it is important toknow which part of the plant is advantagous and which part of this plant as the source ( root, stem,leaf, seed)The extract result comparative between leaves organ and root organ and then to evaluationbase on thin layer chromatografi (TLC) each organ is dominant found Flavokawain, MethysticindanYangonin. The profil organic acid from root and leaves found the same and equal organic acidthat is benzoate acid. Soil type Malang is andosol, kambisol, latosol, alluvial and Soil type Mojokerto62,7% is Alluvial, 37,16% grumosol with rich mineral. Base on etanol exctraction , result thatcontent of bioactive component dominant from plant grow in type soil alluvial.